STRATEGI RANTAI PASOK KELAPA SAWIT DI PROVINSI SUMATERA BARAT - Zulqa, Rahma; Ampuh Hadiguna, Rika (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
Indonesia is a major producer and exporter of CPO (Crude Palm Oil) in the world with a dominance of 56% of total CPO production in the world and 57% of the total exports of countries in the world. According to GAPKI data the volume of CPO oil exports and derivatives during 2018 reached 32.02 million tons. The Sumatra region has the largest oil palm center in Indonesia, West Sumatra is one of the developing provinces and has potential in oil palm plantations with a total production of 568 680.4 tons / year (West Sumatra in Figures, 2019). However, there are sustainability issues that cover environmental, social and economic aspects which are strategic issues globally. This ongoing issue triggers various risks that can harm various parties and must be managed properly. One way to manage this problem is to supply chain efficiency. With the supply chain efficiency, success factors and palm oil supply chain strategies in the Province of West Sumatra can be determined. This research uses descriptive qualitative analysis method through interviews with related respondents and SWOT matrix. The results showed that success factors were found in the garden chain system, transportation from the garden to the factory, factory and transportation to the storage tank and consumers. The palm oil supply chain strategy obtained is the SO, WO, ST, WT strategy. To meet the integrated supply chain system and sustainable development of palm oil in addressing the existing issues, success factors and strategies for the palm oil supply chain in West Sumatra Province are needed in order to compete in the local and foreign markets.